Use of Air Transport for Minor Burns: Is There Room for Improvement?. Issue 5 (September 2016) - Kashefi, Natalie; Dissanaike, Sharmila
Abstract : Since 1981, the number of US burn centers has decreased by 29%, resulting in more long distance referrals to remaining facilities. Air transport is often the only feasible method for remote patients to reach few remaining burn centers. A significant proportion of flown-in patients have minor burns and are discharged within 24 hours, representing potential over-utilization of resources with increased cost to the healthcare system for no perceptible benefit. We explored factors associated with air transport of burns and opportunities for system improvement. Retrospective review of burn patients transferred by air to regional burn center between January 2003 and June 2013. Demographic, injury and clinical outcome data were acquired from the institutional Burn Registry. Minor burns constituted 17.7% of all flown admits (236/1331). Children were more likely to be included in this cohort at 32% vs 21.6% of adults ( P = .0004). The overtriaged cohort had significantly lower % total BSA than accurately triaged cohort (3.3% vs 15%; P = .0001). Subjects with electrical burn injury were twice as likely to be overtriaged than accurately triaged (10.6% vs 5%; P = .002). The average % total BSA in the overtriaged group was 3.3%; the face was most common area burned (47.7%). The average estimate of charges for transfer was between 25, 000 and 30, 000/patient. The incidence of overtriage among flown-in burn patients, approximately 20%, represents substantial unnecessary healthcare expenditure. Improved burn care education, incentives to increase use of telemedicine, and modification of American Burn Association guidelines to include consultation with a burn center rather than automatic transfer are needed to reduce this cost to the healthcare system.